(untitled) (International Journal of Food and Nutritional Sciences, 2023)
In addition to impairing foot function, the alignment of the ankle, knee, and hip may be negatively impacted by flat foot, a prevalent foot condition. Because it changes the distribution of pressure and the position sensation of the foot joints, walking with flat feet is different from walking normally. Instability and impaired motility are symptoms of flat foot, which is caused by imperfect loading. One definition of functional mobility is the capacity to go about one’s daily life unassisted. The purpose of this research is to examine the impact of flat feet on functional mobility and balance in people aged 20–40. Sixty people participated in the test. There were thirty people divided into two groups, A and B. Group A consisted of people with normal arches of the foot. In contrast, those in Group B who suffer from flat feet Both groups are subjected to three tests: the Single Leg Standing test, the Functional Reach test, and the Time Up and Go test. A single observational study was conducted. The outcomes may be seen by comparing the three tests’ results. There was a significant decline in adults’ functional mobility, dynamic balance, and static balance. The results of the Functional Reach Test (P=0.01018), Time Up & Go (P=4.87414E-06), and Single Leg Standing (P=3.33601E-11) were all statistically significant.